Textile Effluent Impact on Rice (Oryza sativa L.) Growth Attributes in Sandy Clay Loam Soil - Rehman, Tanzeem ur; Alam, Tajwar; Kashif Aziz, Muhammad; Shahzad, muhammad; Bashir, Muneeb; Hassan, Javaid; Sadaf, Rimsha (Journal of Agriculture and Veterinary Science, 2024)
The degradation of soil caused by untreated textile effluent poses a significant threat in Pakistan. Therefore, during this study, a pot experiment quantified the impact of untreated industrial effluent on the growth attributes and heavy metal concentration (Cu and Cd) in rice. Wastewater samples were collected from two different industries and the treatments were comprised of control (tape water), Rashid printing textile effluent (RPTE), RPTE (40% dilution), Mamtaz mehal textile effluent (MMTE), MMTE (40% dilution), and RPTE (50% dilution) + MMTE (50% dilution) applied as irrigation water. Samples were evaluated for various traits including heavy metals (Cu and Cd). The highest shoot length cm (28.3) was recorded in the control treatment followed by RPTE (40% dilution) treatment (26.0) having a similar trend for fresh and dry shoot weight (g). The highest root length (7.9 cm) was recorded in the control treatment followed by RPTE (40% dilution) treatment (6.9 cm) and the same trend was observed for fresh and dry root weight (g). A similar trend was observed for tillers plant-1. In the case of heavy metals, the highest Cd shoot concentration (mg kg-1) was recorded in RPTE while the highest Cd concentration in root was recorded in treatment MMTE, and a similar trend was observed for post-harvest soil Cd concentration. Highest shoot Cu concentration (mg kg-1) was recorded for treatment MMTE and the same trend was observed for roots while the highest concentration of Cu for post-harvest soil was recorded for treatment RPTE. The results depicted that the application of contaminated effluent leads to the development of heavy metal toxicity in the soil. Furthermore, higher concentrations of effluent not only exacerbated heavy metal toxicity but also reduced the growth of rice. Therefore, regular monitoring by government agencies is recommended to ensure the production of safe and healthy food.
Keywords: Biomass; Heavy metals; Effluent; Copper; Cadmium; Soil pollution